2019
DOI: 10.3390/pr7110785
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Least Impactful Municipal Solid Waste Management Option in Harare, Zimbabwe

Abstract: Six municipal solid waste management (MSWM) options (A1–A6) in Harare were developed and analyzed for their global warming, acidification, eutrophication and human health impact potentials using life cycle assessment methodology to determine the least impactful option in Harare. Study findings will aid the development of future MSWM systems in Harare. A1 and A2 considered the landfilling and incineration, respectively, of indiscriminately collected MSW with energy recovery and byproduct treatment. Source-separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 60 publications
1
47
0
Order By: Relevance
“…The options for treating these MSW fractions generated should be focused on AD of biodegradable MSW fraction, recycling of at least 20% and incineration of at most 80% of the non-biodegradable fractions. The focus on the mentioned MSW treatment is informed by study findings from [35] which identified the option incorporating AD of organic fraction of MSW, at least 20% and at most 80 percent recycling and incineration of the non-organic MSW fraction generated in Harare respectively being the least environmentally impactful option. Composting of the biodegradable MSW fractions could also be considered after AD due to the better environmental performance and overall edge of AD over composting resulting from its renewable energy production capabilities and other associated benefits noted by [36].…”
Section: Proposals For Mswm Decentralisation In Hararementioning
confidence: 99%
See 3 more Smart Citations
“…The options for treating these MSW fractions generated should be focused on AD of biodegradable MSW fraction, recycling of at least 20% and incineration of at most 80% of the non-biodegradable fractions. The focus on the mentioned MSW treatment is informed by study findings from [35] which identified the option incorporating AD of organic fraction of MSW, at least 20% and at most 80 percent recycling and incineration of the non-organic MSW fraction generated in Harare respectively being the least environmentally impactful option. Composting of the biodegradable MSW fractions could also be considered after AD due to the better environmental performance and overall edge of AD over composting resulting from its renewable energy production capabilities and other associated benefits noted by [36].…”
Section: Proposals For Mswm Decentralisation In Hararementioning
confidence: 99%
“…For example, in Harare only 9.6% of the MSW generated in Harare is recycled translating to only 23,000 tons of the over 467,000 tons generated. At least 20% of the nonbiodegradable MSW equivalent to at least 56,000 tons has to be recycled [35] thus double the current recycling level. To meet this target therefore, recycling could be done at household, institutional and community level.…”
Section: Recyclingmentioning
confidence: 99%
See 2 more Smart Citations
“…WTS apart from their costs abatement capabilities they could possibly bring about reduced environmental impacts of future MSWM systems that could be implemented in Harare city, Chitungwiza, Ruwa, Epworth and Norton. In [22], the authors observed that the recycling of atleast 20% of the recoverable materials contributes to significant reductions of environmental impacts (acidification, eutrophication, human health and global warming) of MSWM options that could be earmarked for future implementation in Harare city, Chitungwiza, Ruwa, Epworth and Norton. WTS have largely been reported that they can act as platforms for recycling and materials recovery hence their incorporation in future MSWM systems as platforms for recycling and materials recovery will result in reduced environmental impacts.…”
Section: Introductionmentioning
confidence: 99%